Determinantes da adesão à terapia Anti-retroviral em crianças infectadas pelo HIV - Flavia Gomes Faleiro Ferreira (2004)
The widespread use of Highly Active Antiretroviral Therapy (HAART) has reduced HIV morbidity and mortality and has changed HIV/AIDS from a severe and acute disease into a chronic disease. Very high levels of adherence to HAART are a prerequisite for a successful virological and immunological response. Low adherence increases the risk of treatment failure and disease progression. For children, factors related to the caregiver and the medications are all considered to be important for good adherence. This study was carried out at the UFMG Pediatric Immunology Clinic from August 2002 to May 2003. The caregivers answered a questionnaire, adapted from the PENTA network, which assesseddifficulties with individual drugs, the most difficult period of the day for giving the doses, reasons for not taking the drugs and how HAART interfered with every day life. Adherence was assessed by number of doses missed in the previous 3 days. Additional information was abstracted from patient charts, clinic database and pharmacy records. Good adherence was defined if 100% of ARV doses were taken in the last 3 days. Eligibility requirements included: more than 3 months of current antiretroviral treatment, receipt of care in the hospital and age < 18 years. Reasons for not participating include: patient who had not been seen in the clinic during the study period and caregiver refusal. Statistical analyses were performed with SPSS software, using univariate analysis, followed by a multivariate logistic regression model. The Kaplan-Meier method was used to study virologic and immunologic failure. 103 children were enrolled in the study (50% of children on current ARVtreatment in the service). Current ARV regimens were: 2 ITRN 15.53%; 3 ITRN 2.9%; 2 ITRN + ITRNN 35.92%; 2 ITRN + PI 41.74%; 4 ARVs 3.8%. Good adherence was reported by 76 (73.7%) subjects no missed doses in the previous 3 days. Adherence was not influenced by age, sex, caregiver education and monthly income. 88 (81.54%) of caregivers reported easily remembering their children ARV regimen and 46 (42.6%) thought it interfered a lot in their daily routine. Forgetfulness was the reason for not taking medications in 48.1%. Nelfinavir and Efavirenz were considered very difficult to take in 27.5% and 26.8%, respectively.AZT, D4T and 3TC were considered easy to take in 80% and 97.5%, respectively. In univariate analysis: first ARV therapy children and one reason for not taken the drugs have better adherence. In multivariate analysis: One reason for not taken the drugs. The Kaplan-Meier survival plot, stratified by adherence group, showed the adherents patients had advantage in maintaining the virologic (log rank= 0.0078) and immunologic (log rank = 0.016) response. The patients in the study have high levels of adherence. Adherence was not influenced by the current ARV regimens. The first ARV therapy have better adherence. There are a lot of reasons for not taking the drugs. The adherent group maintained the virologic and immunologic response more than non-adherent group.